Opacity in Hedge Funds: Does it Create Value for Investors and Managers? - Flávia Januzzi; Aureliano Bressan; Fernando Moreira (BBR: Brazilian Business Review)
This paper investigates if opacity (as measured by derivatives usage) creates value for investors and the managers of hedge funds that charge performance fees. Since we do not identify a positive relation between opacity and managers’ revenue, it is not possible to state that opacity is a source of manager’s value creation for hedge fund investors and managers. However, considering that opacity is positively associated with risk-taking and negatively related with investors’ adjusted returns, we suggest policies aiming at protecting investors, especially those less qualified. We examine a unique and comprehensive database related to the positions in derivatives taken by managers, which was enabled due to specific disclosure regulatory demands of the Brazilian Securities Exchange Commission, where detailed information on hedge funds’ portfolio allocation should be provided on a monthly basis.